Communicating about overdiagnosis: Learning from community focus groups on osteoporosis. - Ray Moynihan; Rebecca Sims; Jolyn Hersch; Rae Thomas; Paul Glasziou; Kirsten McCaffery (PLoS ONE)
Background Overdiagnosis is considered a risk associated with the diagnosis of osteoporosis-as many people diagnosed won't experience harm from the condition. As yet there's little evidence on community understanding of overdiagnosis outside cancer- where it is an established risk of some screening programs-or effective ways to communicate about it. We examined community understanding around overdiagnosis of osteoporosis, to optimise communication strategies about this problem. Methods and findings Using a qualitative design we recruited a community sample of women, 50-80 years, from the Gold Coast community around Bond University, Australia, using random digit dialing, and conducted 5 focus groups with 41 women. A discussion guide and 4-part presentation were developed and piloted, with independent review from a consumer and clinical experts. Initial discussion had 4 segments: osteoporosis; bone density vs. other risk factors; medication; and overdiagnosis. The second half included the 4 short presentations and discussions on each. Analysis used Framework Analysis method. Initially participants described osteoporosis as bone degeneration causing some fear, demonstrated imprecise understanding of overdiagnosis, had a view osteoporosis couldn't be overdiagnosed as bone scans provided "clear cut" results, expressed belief in early diagnosis, and interest in prevention strategies enabling control. Following presentations, participants expressed some understanding of overdiagnosis, preference for describing osteoporosis as a "risk factor" not "disease", concern about a poor risk-benefit ratio for medications, and surprise and unease the definition of osteoporosis decided bone density of young women was "normal", without age adjustment. Limitations include English-speaking backgrounds of the sample and complex materials. Conclusions Our findings suggest a gap between community expectations and how experts sometimes arbitrarily set low diagnostic thresholds which label those at risk as "diseased". Optimal communication about overdiagnosis could build on community scepticism about treatments, encouraging weighing up benefits and harms of tests and diagnoses, and framing this information as positively adding to knowledge.